2021
DOI: 10.1007/s00415-021-10725-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in adult brainstem glioma: a tertiary care center analysis and review of the literature

Abstract: Introduction Adult brainstem gliomas (BSGs) are rare central nervous system tumours characterized by a highly heterogeneous clinical course. Median survival times range from 11 to 84 months. Beyond surgery, no treatment standard has been established. We investigated clinical and radiological data to assess prognostic features providing support for treatment decisions. Methods 34 BSG patients treated between 2000 and 2019 and aged ≥ 18 years at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 70 publications
0
4
1
Order By: Relevance
“…Brainstem gliomas remains a challenging tumor type due to their highly heterogenous clinical features, with many clinical trials failing to improve survival. Several studies have found that older age, lower KPS, higher tumor grade and appearance of necrosis are unfavorable prognostic factors for survival [32][33][34]. In our case series, however, age, KPS, and tumor grade did not appear to affect the efficacy of BNCT.…”
Section: Discussioncontrasting
confidence: 70%
“…Brainstem gliomas remains a challenging tumor type due to their highly heterogenous clinical features, with many clinical trials failing to improve survival. Several studies have found that older age, lower KPS, higher tumor grade and appearance of necrosis are unfavorable prognostic factors for survival [32][33][34]. In our case series, however, age, KPS, and tumor grade did not appear to affect the efficacy of BNCT.…”
Section: Discussioncontrasting
confidence: 70%
“…For example, brainstem glioma can have a few categories of glioma in different more specific sites, such as diffuse intrinsic pontine glioma (DIPG) with very poor survival and exogenous medulla glioma with excellent survival after successful operation. 20 It is convinced that only a well-designed brain tumour patients’ registry can provide more details on brain tumour patient characteristics as well as the disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Leibetseder and collaborators studied the clinical and radiological parameters possibly influencing the prognosis of patients with brainstem gliomas (BSG). The ECOG Performance Status scale, the body mass index, the WHO grade and the ADC were proposed as possible parameters associated with the OS of BSG patients [132]. The prognosis of HGG patients is worse with advancing age.…”
Section: Clinical Studiesmentioning
confidence: 99%